Рецензія на монографію “Студії з прикладної фразеології: лінгводидактика, навчальна фразеологія, контрастивна фразеологія”. Г. Кузь. Пряшів : Вид-во Пряшівського ун-ту, 2024. 212 с. - Даскалюк, Оксана Любомирівна (Актуальні питання суспільних наук та історії медицини : спільний українсько-румунський науковий журнал, 2024)
The proposed monograph presents studies that deal with various aspects of including phraseology in learning the Ukrainian language as foreign. The effectiveness of communication, in addition to knowledge of the language, also depends on other factors: conditions and culture of communication, rules of etiquette, understanding of non-verbal forms of expression, social norms of linguistic and non-verbal behaviour, and availability of deep background knowledge.
Keywords: monograph, linguistic didactics, phraseology, linguistic culture, phraseography.